2016
DOI: 10.3389/fneur.2016.00238
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Segmental Diameter of the Healthy Human Spinal Cord

Abstract: Knowledge of the average size and variability of the human spinal cord can be of importance when treating pathological conditions in the spinal cord. Data on healthy human spinal cord morphometrics have been published for more than a century using different techniques of measurements, but unfortunately, comparison of results from different studies is difficult because of the different anatomical landmarks used as reference points along the craniocaudal axis for the measurements. The aim of this review was to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 26 publications
1
86
0
2
Order By: Relevance
“…[10][11][12] In our study, the AP diameter of spinal cord was greatest at C1 and it gradually decreased from 7.74 mm at C1 in males and 6.63 mm in females with the lowest at C7 vertebrae. This finding was in line with that of Frostell A et al 13 who also observed that the AP diameter was greatest at C1 (8.3mm) and gradually decreased till C7 (6.9mm). In the present study, however, gender wise there was statistically significant difference between the AP diameters at C1, C2 and C3 (P value <0.05) and not between that of C4, C5, C6 an C7.…”
Section: Cervical Cord Parameterssupporting
confidence: 92%
“…[10][11][12] In our study, the AP diameter of spinal cord was greatest at C1 and it gradually decreased from 7.74 mm at C1 in males and 6.63 mm in females with the lowest at C7 vertebrae. This finding was in line with that of Frostell A et al 13 who also observed that the AP diameter was greatest at C1 (8.3mm) and gradually decreased till C7 (6.9mm). In the present study, however, gender wise there was statistically significant difference between the AP diameters at C1, C2 and C3 (P value <0.05) and not between that of C4, C5, C6 an C7.…”
Section: Cervical Cord Parameterssupporting
confidence: 92%
“…While the majority of our cohort spinal cords were dissected and labelled according to neuronal segmental level of the cord, all controls and several ALS cords were dissected according to bony vertebral segmental level, therefore we first measured and plotted the transverse diameters of all spinal cord segments for each case. For cases cut according to vertebral level, we then employed a conversion scheme to relabel the segments according to neuronal level [30]. After relabelling (Fig 2A,B), the average transverse diameter for control and ALS spinal cords peaked at C5, but ALS cords were narrower at C5 (diameter 9.80 ± 0.43 mm) than controls (diameter 11.71 ± 0.23 mm, Fig 2B, p = 0.022).…”
Section: Resultsmentioning
confidence: 99%
“…Three spinal cord regions were analysed: cervical (C8), mid-thoracic (T7-T9), and lumbar (L4/L5). To select the appropriate segmental block for each case we first measured the transverse diameters of all spinal cord segments with Vernier callipers (Fig S1A) and compared them with population estimates of segmental diameter (Fig S1B) [30]. This demonstrated the disparity between cords sectioned and labelled according to vertebral level compared to neuronal level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, normal values have been reported to range from 20° to 35° for C2 to C7 [13]. A study conducted in 369 subjects of different occupations, researchers observed that cervical hypolordosis is the commonest defect, which leads to painful neck syndrome and to serious compression of cervical nerve roots [14]. Previous studies showed length changing of the spinal cord in flexion and extension.…”
Section: Discussionmentioning
confidence: 99%